Role of Family in Caring Patient with Post Stroke at Home: A Systematic Review - Choliq, Idham; Nasrullah, Dede; Sukadiono (International Journal of Psychosocial Rehabilitation, 2020)
Stroke is a disease that can cause cognitive impairment or disability. Role and support of family as the closest person is necessary for the post-stroke recovery process. This systematic review aims to identify the effectiveness of the family’s role in caring patient with post-stroke at home. There are four steps to define the topic (1) to identify appropriate keywords (post-stroke, community, family, and home), (2) to identify relevant literature based on topic, (3) to identify appropriate inclusion criteria, (4) to analyze the account of various intervention on literature. Search strategy resulted in 849 articles from Scopus, Proquest, Science Direct and SpringerLink with a limit of 2014-2018 and English-language, only 15 journals were eligible for analysis. There are types of family roles to support patient’s post-stroke at home: Activity daily life (ADL) assistance and psychosocial support. The role and support of family put effect into the caring patient with stroke at home, including an increase of ADL, life quality, cognitive function, and self-efficacy